2020
DOI: 10.1071/an18771
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variations in leaf traits, chemical composition and in vitro true digestibility of four temperate fodder tree species

Abstract: Context Many tree and shrub species are underestimated fodder resources due to insufficient knowledge about their potential feeding value, especially for goats. Aims The present work aimed at assessing productive and nutritional attributes of the foliage of the following four temperate tree species widespread in Europe: Acer pseudoplatanus, Fraxinus excelsior, Salix caprea and Sorbus aucuparia. Methods Leaf length and biomass, proximate composition, fatty acid profile, phenolic composition and in vitro true … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 63 publications
(81 reference statements)
4
8
0
Order By: Relevance
“…The chemical traits of browsed species were extremely wide, which are in accordance with previous studies conducted in northern and eastern Mediterranean forest rangelands [ 6 , 12 , 13 , 14 ], deciduous tropical forest [ 35 ], South African rangeland [ 36 ]. In northwestern Italy, Ravetto Enri et al [ 37 ] reported the relevant effect of the vegetative season on chemical composition and in vitro true digestibility of four tree species selected by goats. These wide variations on the nutritional proprieties of plant species could be explained by soil fertility [ 15 , 38 ], environmental conditions, and stage of growth or age [ 14 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The chemical traits of browsed species were extremely wide, which are in accordance with previous studies conducted in northern and eastern Mediterranean forest rangelands [ 6 , 12 , 13 , 14 ], deciduous tropical forest [ 35 ], South African rangeland [ 36 ]. In northwestern Italy, Ravetto Enri et al [ 37 ] reported the relevant effect of the vegetative season on chemical composition and in vitro true digestibility of four tree species selected by goats. These wide variations on the nutritional proprieties of plant species could be explained by soil fertility [ 15 , 38 ], environmental conditions, and stage of growth or age [ 14 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concurrently, several variables, including inherent species genotype [ 18 ], seasonal variance [ 19 – 21 ], site capacity, edapho-climatic factors [ 22 ] and management aspects [ 23 ], contribute in determining the nutritional quality dynamics of fodder trees. Among these, temporal fluctuation in the chemical composition and digestibility of tree species may occur as a result of phenological and climatic variations [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Concurrently, several variables, including inherent species genotype [ 18 ], seasonal variance [ 19 – 21 ], site capacity, edapho-climatic factors [ 22 ] and management aspects [ 23 ], contribute in determining the nutritional quality dynamics of fodder trees. Among these, temporal fluctuation in the chemical composition and digestibility of tree species may occur as a result of phenological and climatic variations [ 21 ]. Thus, knowledge of tree foliage mineral and nutrient fluctuations during the seasons offers considerable potential to provide high-quality ruminant forage [ 19 ], by selecting an appropriate harvesting period for specific tree species in a particular agro-climatic region [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fraxinus ornus is acknowledged as an important browse species for goats in Mediterranean environments (Papachristou et al 1999 ; Papachristou and Papanastasis 1994 ). Fraxinus excelsior , which has high forage quality (Hejcmanová et al 2014 ; Ravetto Enri et al 2020 ), was positively selected by cows too, except in Torrette study area. The avoidance for this species observed in Torrette may be explained by the age of the plants, as in this paddock there were abundant F. excelsior seedlings about 20-cm tall, whereas in the other sites the trees were mainly adult and the cows fed on their lowest branches.…”
Section: Discussionmentioning
confidence: 93%